Where your treasure is Psalms that summon you from self to community - Peterson, Eugene H., 1932- (Grand Rapids, MI William B. Eerdmans, 1985)
Includes bibliographical references.
Keywords: Bible. O.T. Psalms -- devotional material; Christianity and politics -- Biblical teaching